Cryptococcus neoformans Mar1 function links mitochondrial metabolism, oxidative stress, and antifungal tolerance - Telzrow, Calla L.; Esher Righi, Shannon; Cathey, Jackson M.; Granek, Joshua A.; Alspaugh, J. Andrew (Frontiers in Physiology, 2023)
Microbial pathogens undergo significant physiological changes during interactions with the infected host, including alterations in metabolism and cell architecture. The Cryptococcus neoformans Mar1 protein is required for the proper ordering of the fungal cell wall in response to host-relevant stresses. However, the precise mechanism by which this Cryptococcus-specific protein regulates cell wall homeostasis was not defined. Here, we demonstrate that C. neoformans Mar1 is highly enriched in mitochondria. A mar1 loss-of-function mutant strain is impaired in growth in the presence of select electron transport chain inhibitors, has altered ATP homeostasis, and promotes proper mitochondrial morphogenesis. Pharmacological inhibition of complex IV of the electron transport chain in wild-type cells promotes similar cell wall changes as the mar1 mutant strain, supporting prior associations between mitochondrial function and cell wall homeostasis. Although Mar1 is not required for general susceptibility to the azole antifungals, the mar1 mutant strain displays increased tolerance to fluconazole that correlates with repressed mitochondrial metabolic activity. Together, these studies support an emerging model in which the metabolic activity of microbial cells directs cell physiological changes to allow persistence in the face of antimicrobial and host stress.